Analysis of the concept of «social capital» in literature - D.M. (Економіка, управління та адміністрування)
The article deals with an overview of existing literature on various aspects related to social capital (definition, conceptual frameworks, empirical research, etc.), and analyzes economic literature on the definition of social capital. The main mechanisms for disseminating knowledge based on social capital are also considered. There are several social capital definitions. These definitions can be divided into two categories: social capital is internal – as an asset created because of partner interaction and within the social network and/or external – formed through confidence in institutions and under the influence of social norms in society. A modern interpretation of social capital is that this is the result of interconnections of financial, manufactured, human, intellectual, and natural capital that increases management efficiency, activates the potential capabilities of the enterprise. An analysis of the definitions of social capital and its forms of expression allowed us to schematically reflect the relationship between structural elements of social capital: trust, social network, and social norms. Modern practice and requirements of investors regarding the information transparency of corporate reporting and business accountability, due to a deeper understanding of the company’s strategy and tools for its implementation, explains the transformation of approaches to the formation of corporate reporting. The reflection of social capital in reporting acquires importance, since it directly affects the increase in transparency, and, accordingly, affects the enterprise market value. Effective use of social capital allows to reduce transaction costs and increase financial performance.